Renewable energy in East Asia towards a new developmentalism - Dent, Christopher M. 1965- (Routledge contemporary Asia series, 2014)
This book presents a comprehensive study of renewable energy development in East Asia. It begins by examining renewable energy development in global and historic contexts, and situates East Asia's position in the recent worldwide expansion of renewables. This same approach is applied on sector-specific chapter studies on wind, solar, hydropower, geothermal, ocean (wave and tidal) and bioenergy, and to general trends in renewable energy policy. Governments play a critical role in promoting renewables and their contribution to tackling climate change and other environmental challenges. Christopher M. Dent argues this is particularly relevant to East Asia, where state capacity practice has been increasingly allied to ecological modernisation thinking to form what he calls 'new developmentalism', the principal foundation on which renewables have developed in the region as well as how East Asia's low carbon development is being generally promoted.